Part I – January 1968 - Papers - The Thermal Stability of the Beta Prime Occurring in the Ag-Zn and Ag-Au-Zn Systems - M. E. Brookes; R. W. Smith (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1969)
The temperature at which th: quenched 0' (ordered bcc) phase transfo.rms to the ( (complex hexagonal) phase on heating has been examined for certain Ag-Zn and Ag-Au-Zn alloys using an electrical resistivity method. The transition temperature decreases by approxinzately 7°C as the zinc content is reduced by 1 at. pct. The critical temperature, Tc, for long-range order has also been measured for a number of Ag-Au-Zn alloys. Extrapolation to zero gold content suggests that Tc decreases by approximately 5°C per 1 at. pct reduction in zinc content. The 0 phase of the Ag-Zn system exists over a narrow range near the composition Ag zn,' Fig. 1, and has a bcc structure which is disordered above 272°C. Slow cooling to temperatures below the range 274"/258"C allows the complex hexagonal phase, r° to form.2 This is the stable structure at room temperature.3 Upon quenching 0 -phase alloys from high temperatures, it is found that the 0 — (' transformation is suppressed; but ordering takes place (i.e., 0 -0'). This ordered structure can also be obtained by the room-temperature aging of cold-worked (0.4 Deformation of the 0' phase gives rise to a fur- ther hexagonal phase ( (of nearly ideal axial ratio) which reverts to b' within a few hours.= In view of this, it has been suggested that the equilibrium struc-